„Tu și alte femei” de Dumitru Crudu sau fantasma iubirii totale - PILCHIN, Maria (BIBLIOPOLIS, 2026)
The microstudy reads “You, and Other Women” (Cartier, 2025) by Dumitru Crudu as a narratological device of desire, built through repetition, substitution, and self-reflexivity. The epigraph dedicated to Gheorghe Crăciun and the intertext with “The Beauty without a Body” establish a reading pact in which the female body appears as both intense presence and constitutive absence, converted into sign and projection. The novel functions like a matryoshka doll: from one feminine face, others emerge, not as realist variety but as variations of the same phantasmatic-affective structure. The protagonist’s onomastic instability (Cosmin Dimitri / Cosmin Dumitru / Mircea) frames identity as an effect of discourse: a mobile, vulnerable self repeatedly re-named and re-positioned. The serial catalogue of women (Iulia, Tania, Livia, Natașa, Sveta, Beatrice, etc.) reactivates the promise of “total” love that renews itself through failure, while Iulia’s appearance-and-flight defines erotic attachment as choreography of distance. In the background, the post-communist transition and the latent trauma of deportations shape a moral ecology of precariousness. Writing becomes therapy and a technique of survival, and the figures of Sveta and Beatrice gesture – without triumphalism – towards a possible exit from the automatisms of substitution. Finally, ironic self-referentiality, with the author turned into a character, dismantles the myths of confession and authenticity.